Editorial: Aquatic microorganism and their response to environment virulence and antimicrobial resistance - Deng, Yiqin; Fu, Songzhe; Lee, Learn-Han *; Feng, Juan; Huang, Jie (Frontiers Media, 2023)
Overloaded or poorly managed farming systems, in synergy with emissions from intensive human activities and unstable climate systems arising from global climate change, can lead to environmental degradation, create imbalances in microecosystems, and result in pathogen blooms. These issues can significantly impact aquaculture and human health, leading to frequent outbreaks of bacterial infections and greatly increasing the risk of antibiotic resistance. Therefore, ensuring the health of aquatic animals and humans requires maintaining an early detection system for diseases, constantly monitoring the usage of antimicrobial agents (AMU), establishing national surveillance programs for antimicrobial resistance (AMR), and providing guidance for their application and prudent use, and actively promoting environment/ecosystem friendly strategies for disease management.